Our elders teach us : Maya-Kaqchikel historical perspectives : xkib'ij kan qate' qatata' - Carey, David, Jr., 1967- (Contemporary American Indian studies., 2001)
"Combining the methodologies of anthropology and history, Carey used both oral interviews and meticulous archival research to construct a history of the last 50 years in Guatemala from the perspective of present-day Mayan people. His research took place over five years and included intensive language study, four summers of fieldwork, and a yearlong residence in Comalapa, during which he conducted most of the 414 interviews. By casting a wide net for his interviews - from tiny hamlets to bustling Guatemala City - Carey gained insight into more than a single community or a single group of Maya."--Jacket